[Retracted Article] Histopathology of liver and kidney of the selected mesopelagic fishes from the Andaman Sea, Thailand - Senarat, Sinlapachai; Sudtongkong, Chanyut; Kettratad, Jes; Mongkolchaichana, Ezra; Jiraungkoorskul, Wannee; Para, Chamnan; ongkamhaeng, Koraon (YRU Journal of Science and Technology, 2020)
The study on the health status of mesopelagic fishes is very scanty and is not included in the Andaman Sea, Thailand. The histopathology of livers and kidneys of three selected mesopelagic fishes, including Atherinomorus pinguis, Gavialiceps javanicus and Alepocephalus bicolor from the Andaman Sea, was hence focused using histological technique. Seven representative samples from each fish species were collected in October 2018. From the study on hepatic histopathology, it was found that the current study further demonstrated necrosis (Nc) occurred in A. pinguis while accumulations of melanomacrophage center (MMC) found in all three species: pyknotic nuclei (Pn), karyolysis (Kl), and vacuolar degeneration (Vd) in G. javanicus. From the study of renal histopathology, it was observed that degeneration of renal tubule (Drt) and accumulations of melanomacrophage center (MMC) found in all three species. Pyknotic nuclei (Pn) and karyolysis (Kl) were also recorded in A. bicolor and G. javanicus. It concluded that all histopathological lesions indicated the reduced functions of both liver and kidney of three species inhabited in mesopelagic zone of the Andaman Sea of Thailand.